2020
DOI: 10.30802/aalas-cm-19-000022
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Comparison of the Dura Mater among Species

Abstract: The biocompatibility, biodegradation, feasibility, and efficacy of medical devices like dural sealants and substitutes are often evaluated in various animal models. However, none of these studies explain the rationale for choosing a particular species, and a systematic interspecies comparison of the dura is not available. We hypothesized that histologic characteristics of the dura would differ among species. We systematically investigated basic characteristics of the dura, including thickness, composition, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…Histological assessment of the dura of different species showed that porcine dura closely resembles the human dura. 9 We therefore performed a relatively large bilateral craniotomy with a large exposure of the dura in which a representative amount of sealant was applied. A second strength was the strict protocol adherence and objective results evaluation; the surgery was performed by a full trained neurosurgeon, the MRI follow up was done by a veterinary radiologist and the histological follow up was done by a veterinary pathologist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological assessment of the dura of different species showed that porcine dura closely resembles the human dura. 9 We therefore performed a relatively large bilateral craniotomy with a large exposure of the dura in which a representative amount of sealant was applied. A second strength was the strict protocol adherence and objective results evaluation; the surgery was performed by a full trained neurosurgeon, the MRI follow up was done by a veterinary radiologist and the histological follow up was done by a veterinary pathologist.…”
Section: Discussionmentioning
confidence: 99%
“…Pig dura is 0.30 (±0.08) mm thick on average. 9 MRI measurements of dura plus sealant showed a mean thickness of 0.9 (±0.3) mm at 3 days, 2.0 (±1.2) mm at 14 days and 2.1 (±0.4) mm at 1 month. At 6 and 12 months no sealant was visible anymore on MRI.…”
Section: Mri Follow-upmentioning
confidence: 93%
“…ArtiFascia and the Control device are indicated to repair human dura, a 0.5- to 1-mm-thick soft connective tissue. The rabbit’s dura is significantly thinner (99 µm in rabbit vs 564 in human), 27 and we estimated that this structural difference caused both implants to occupy the space where once the drilled bone piece was located. Consistent with this, Figures 3E and F show a relatively large empty cavity where the Control graft was implanted.…”
Section: Discussionmentioning
confidence: 99%
“…Neodura is defined by a well-delineated layer of densely collagenous connective tissue situated between newly formed bone and the brain surface or deep within the surgical fibrous scar that is parallel to the leptomeninges and of a thickness of the order of the normal dura. 27 A fibrous scar is typically thicker, not tangentially polarized and follows the surgical planes rather than the brain surface.…”
Section: Animals Materials and Methodsmentioning
confidence: 99%
“…The dura mater is the outermost layer of the meninges that cover the central nervous system. It consists predominantly of collagen and elastin and possesses viscoelastic properties necessary to solve its biological functions [ 25 , 26 , 27 ]. Many biomaterials and sealants are used for dural closure, but the results are suboptimal.…”
Section: Introductionmentioning
confidence: 99%